Headaches and sleep problems in US adolescents: Findings from the National Comorbidity Survey – Adolescent Supplement (NCS-A). (September 2019) - Lateef, Tarannum; Witonsky, Kailyn; He, Jianping; Ries Merikangas, Kathleen
Background: There is limited research on the association of sleep problems with International Classification of Headache Disorders (ICHD-II)-defined headache subtypes in youth, particularly from community-based samples. This cross-sectional study examines the associations of sleep patterns, symptoms and disorders with specific headache subtypes among adolescents from the general population of the United States. Methods: The sample includes 10, 123 adolescents in the National Comorbidity Survey – Adolescent Supplement, a face-to-face survey of adolescents aged 13–18 years in the continental USA. Headache subtype diagnoses were based on modified ICHD-III criteria, and mood and anxiety disorders were based on Diagnostic and Statistical Manual of Mental Disorders criteria. The associations of self-reported sleep patterns and insomnia symptoms and headache status were estimated with multivariate regression models that adjust for demographic characteristics and comorbid anxiety and mood disorders. Results: There was no significant difference in bedtime between youth with and without headache. However, adolescents with migraine headache reported significantly shorter sleep duration ( p  = .022) and earlier wakeup time ( p  = .002) than those without headache. Youth with any headache, particularly migraine, had significantly more sleep disturbances than those without headache. With respect to headache subtypes, youth with migraine with aura were more likely to report difficulty maintaining sleep, early morning awakening, daytime fatigue, and persistent insomnia symptoms than those with migraine without aura. However, these associations were largely accounted for by comorbid anxiety and mood disorders. There was a monotonic increase in the number of insomnia symptoms with increasingly restrictive definitions of migraine. Conclusion: Pervasive sleep disturbances in adolescents with headache have important implications for the evaluation, treatment and etiology of pediatric headache.